(untitled) (Bangladesh Journal of Agriculture, 2024)
Chilli peppers, integral to Capsicum spp., are globally vital crops valued for culinary, economic, and nutritional contributions. Assessing genotypes is essential for improving varieties with traits like higher yield, disease resilience, and enhanced nutritional value. This study was conducted at the Spices Research Centre in Shibganj, Bogura, during the period of 2019-20 to evaluate 20 genotypes of chilli. Employing an alpha lattice design with two replications, the evaluation considered genetic diversity, variation, heritability, clustering, and trait associations as key components. All the traits exhibited remarkable significance ( < 0.01) for the studied genotypes, underscoring the genetic variability inherent to the traits in focus. Heritability varied from 79% to 99% for the traits investigated. Foremost in yield was found in the AVPP 1111 genotype (21.62 t/ha), trailed by the Indch 39 (21.19 t/ha), and A1511050 (20.57 t/ha). The cluster analysis dendrogram visually demonstrated the proximity among different genotypes concerning their similarities, ultimately forming six distinct clusters. While the studied traits displayed higher genotypic co-efficient of variation (GCV), and phenotypic co-efficient of variation (PCV) values, however, GCV values were closely aligned with PCV values across the traits. Notably, a robust positive correlation existed between yield and both single fruit weight and the weight of fruit per plant. The outcomes of this study, i.e., the promising genotypes AVPP 1111, Indch 39, A1511050 etc.; grouping; and significant positive correlations of different traits with grain yield, hold valuable insights for future chili improvement initiatives. Bangladesh J. Agri. 2024, 49(1): 95-105